2016
DOI: 10.1002/ijc.30476
|View full text |Cite
|
Sign up to set email alerts
|

Differences in survival for patients with familial and sporadic cancer

Abstract: Family history of cancer is a well-known risk factor but the role of family history in survival is less clear. The aim of this study was to investigate the association between family history and cancer survival for the common cancers in Sweden. Using the Swedish population-based registers, patients diagnosed with the most common cancers were followed for cancer-specific death during 1991-2010. We used multivariate proportional hazards (Cox) regression models to contrast the survival of patients with a family h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Ambiguous AT and CG genetic variants were excluded and out of 124 tested variants only 52 risk variants were also associated with worse OS (proportion of risk variants associated with worse OS 41%, 95% CI = 33–51%) and 58 were associated with decrease in CSS (proportion of risk variants associated with worse CSS 47%, 95% CI = 38–56%). Though not reaching suggested significance level ( p ≤ 0.05), these results are consistent with directions of effects observed in previous studies …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Ambiguous AT and CG genetic variants were excluded and out of 124 tested variants only 52 risk variants were also associated with worse OS (proportion of risk variants associated with worse OS 41%, 95% CI = 33–51%) and 58 were associated with decrease in CSS (proportion of risk variants associated with worse CSS 47%, 95% CI = 38–56%). Though not reaching suggested significance level ( p ≤ 0.05), these results are consistent with directions of effects observed in previous studies …”
Section: Resultssupporting
confidence: 55%
“…Though not reaching suggested significance level (p ≤ 0.05), these results are consistent with directions of effects observed in previous studies. 3,4 None of the nominally significant genetic variants have known detrimental clinically relevant effects on gene function (Supporting Information Table S6). Rs3087967, which is located 3'UTP of C11orf53, is known to be associated with higher COLCA2 and C11orf53 expression in colon transverse tissue for C allele.…”
Section: Resultsmentioning
confidence: 99%
“…6,8,9,32 The presence of familial cancer in stomach, breast, prostate, and colon cancer patients had protective effects, as in our HCC series, but no such effects were seen for brain and ovarian cancers. 6,8,9 The univariate findings in a study by a group in Hong Kong pointed to better survival in familial HCC patients (who accounted for approximately 10% of the total), especially in an early-stage non-metastatic sub-cohort, a result that appears to resemble the present findings based on a more intensive and less confounded analysis. 19 Although another Chinese investigation with 12% familial cases did not find a significant relationship between family history of HCC and survival after resection, the fact that it was restricted to surgical patients limits its generalizability.…”
Section: Survival Analysis Stratified By Stage Of Hccmentioning
confidence: 49%
“…Second, genetic differences in inherent tumor biology between patients with and without a family history may influence cancer mortality . A Swedish population‐based study found a higher proportion of indolent subtypes in familial leukemia, whereas familial cases of ovarian cancers had a more aggressive course with poorer survival . Functional genetic or immunologic polymorphisms may well determine not only susceptibility to specific diseases, but also individual responses to cancer treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation